PENGARUH CALLING DAN PERSEPSI DUKUNGAN ORGANISASI TERHADAP KETERIKATAN KERJA PADA PEGAWAI GENERASI MILENIAL KANTOR IMIGRASI KELAS I TPI BANDA ACEH - Khadijah Khadijah; Mega Wati (Departemen Manajemen, 2020)
Abstract: This study aims to meansure the effect of Calling and Perceived Organisational Support on Work Enggagement at Millenial Generation Civil Servant in Immigation Class I TPI Banda Aceh. The sample used in this study was Millenial Generation Civil Servant in Immigation Class I TPI Banda Aceh, which amounted to 52 respondent. Data collection equipment used in this study is a questionnaire. The Sampling technique use is Non-probability sampling that is sampling that does not provide the same opportunity for each element or member og population to be selected as a sample. Multiple linear regression is used as an analytical method ti determine thr effect of all the variables involved. The results showed that the independent variable Calling and Perceived Organisational Support had a positive and significant effect (sig 0.05) on the Work Engagement at Millenial Generation Civil Servant in Immigation Class I TPI Banda Aceh with a regression coefficient of Calling (X1) 0.581 Perceived Organisational Support (X2) 0.495. Simultaneous Calling and Perceived Organisational Support variables have a significant effect on Work Engagement at Millenial Generation Civil Servant in Immigation Class I TPI Banda Aceh. And the implications of the research results for the Class I Immigration Office of TPI Banda Aceh are to show great concern for employees (X2.8) because the results of the study show that one of the lowest items is in order to increase their work engagement and pay attention to the sample size and its characteristics for higher accuracy.